1964
DOI: 10.1111/j.2042-7158.1964.tb07414.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various drugs on carrageenin-induced oedema in the rat hind paw

Abstract: Local oedema in the rat hind paw is induced by subplantar injection of a 1% suspension of carrageenin. An assay procedure for the analysis of inhibitory effects of drugs on this inflammatory process is described. The results obtained with a single oral dose of 14 antirheumatic drugs (3 steroids and 11 non-steroids) and of 49 substances without established clinical antirheumatic value are reported. Only 8 compounds were found to be completely devoid of anti-carrageenin activity. Others were active at dose level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

1966
1966
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 9 publications
0
20
0
2
Order By: Relevance
“…The development of the inflammatory response induced by carrageenan (paw edema and pleurisy) is characterized by an initial stage (1-2 h) which is dependent on the release of histamine, serotonin and bradykinin, followed by a later stage (3-4 h) which is maintained principally by the release of prostanoids (Crunkhorn & Meacock, 1971;Niemegeers et al, 1964). It has also been shown that nitric oxide (NO) has an important role as much as in the regulation of vascular permeability as in cell migration induced by proinflammatory agents, including carrageenan (Vinegar et al, 1982;Costa et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The development of the inflammatory response induced by carrageenan (paw edema and pleurisy) is characterized by an initial stage (1-2 h) which is dependent on the release of histamine, serotonin and bradykinin, followed by a later stage (3-4 h) which is maintained principally by the release of prostanoids (Crunkhorn & Meacock, 1971;Niemegeers et al, 1964). It has also been shown that nitric oxide (NO) has an important role as much as in the regulation of vascular permeability as in cell migration induced by proinflammatory agents, including carrageenan (Vinegar et al, 1982;Costa et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…and Table 1.). The inhibitory effect of chlorpromazine on the delayed phase may depend on its membrane stabilizing activity (24,25) rather than its tranquilizing activity, because haloperidol, which possesses about 30 times more potent tranquilizing activity and 3 times more potent anti-edema activity (26,27) and one third to one thirty times less anti histaminic activity than chlorpromazine (28), did not inhibit the delayed phase as is shown in Table 1. Sigg et al (29) and Yamasaki et al (30) reported that antihistaminics, chlor promazine and non-steroidal anti-inflammatory agents inhibited mast-cell degranulation, while steroidal anti-inflammatory agents did not.…”
Section: Combined Effect Of Antihistaminic and Anti-inflannnator;i° Amentioning
confidence: 95%
“…The results of the present study showed that methanol extract of P. major significantly inhibited the formation of the rat paw edema in the early and late phases. Most of the anti-inflammatory medicines are effective in the last phase of edema formation [37]. As shown in Table 2, standard drug diclofenac sodium showed significant inhibition of edema at 4 th hr (81.48%).…”
Section: In Vivo Anti-inflammatory Activitymentioning
confidence: 87%